2013
DOI: 10.1371/journal.pone.0056736
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Acutely Improves Cerebral Blood Flow and Attenuates Moderate Ischemic Injury via an Endothelial Mechanism in Mice

Abstract: Electroacupuncture (EA) is a novel therapy based on traditional acupuncture combined with modern eletrotherapy that is currently being investigated as a treatment for acute ischemic stroke. Here, we studied whether acute EA stimulation improves tissue and functional outcome following experimentally induced cerebral ischemia in mice. We hypothesized that endothelial nitric oxide synthase (eNOS)-mediated perfusion augmentation was related to the beneficial effects of EA by interventions in acute ischemic injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 47 publications
4
62
0
Order By: Relevance
“…By reading the full text of the remaining 208 articles which reported the efficacy of BBA in animal models of focal cerebral ischemia, 54 studies were excluded because the outcome measure was neither neurological function score (NFS) nor infarct volume (IV); 48 studies were excluded because other forms of acupuncture or TCM were used in control group; 34 were excluded because of combination with body acupunctures; 18 studies were removed due to the deficiency of useful data and the problem of duplicate publication. Ultimately, 54 eligible studies were identified (Figure 1)34353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879; Li JA, unpublished Master's thesis, 2005; Wang C, unpublished Master's thesis, 2005; Jin JF, unpublished PhD thesis, 2005; Luo T, unpublished Master's thesis, 2006; Chen X, unpublished Master's thesis, 2007; Ding J, unpublished Master's thesis, 2007; Wang EL, unpublished PhD thesis, 2008; Wu HY, unpublished PhD thesis, 2010.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By reading the full text of the remaining 208 articles which reported the efficacy of BBA in animal models of focal cerebral ischemia, 54 studies were excluded because the outcome measure was neither neurological function score (NFS) nor infarct volume (IV); 48 studies were excluded because other forms of acupuncture or TCM were used in control group; 34 were excluded because of combination with body acupunctures; 18 studies were removed due to the deficiency of useful data and the problem of duplicate publication. Ultimately, 54 eligible studies were identified (Figure 1)34353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879; Li JA, unpublished Master's thesis, 2005; Wang C, unpublished Master's thesis, 2005; Jin JF, unpublished PhD thesis, 2005; Luo T, unpublished Master's thesis, 2006; Chen X, unpublished Master's thesis, 2007; Ding J, unpublished Master's thesis, 2007; Wang EL, unpublished PhD thesis, 2008; Wu HY, unpublished PhD thesis, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…The time of ischemia varied from 30 minutes to 3 hours. Chloral hydrate were used in 32 studies (n = 59.2%) to induce anesthesia, isoflurane in 7 studies34353642455771, Pentobarbital in 9 studies383940414344464760, urethane59 and thiopental69 in one study respectively, while no report of anesthetics in the remaining 4 studies66677879.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ischemia was induced by occluding the MCA, as described previously [16,17]. Size of the cerebral infarct was determined on 2,3,5-triphenyltetrazolium chloride (TTC)-stained, 2 mm-thick brain section.…”
Section: Focal Cerebral Ischemiamentioning
confidence: 99%